2019
DOI: 10.1073/pnas.1908157116
|View full text |Cite
|
Sign up to set email alerts
|

TROPOMI reveals dry-season increase of solar-induced chlorophyll fluorescence in the Amazon forest

Abstract: Photosynthesis of the Amazon rainforest plays an important role in the regional and global carbon cycles, but, despite considerable in situ and space-based observations, it has been intensely debated whether there is a dry-season increase in greenness and photosynthesis of the moist tropical Amazonian forests. Solar-induced chlorophyll fluorescence (SIF), which is emitted by chlorophyll, has a strong positive linear relationship with photosynthesis at the canopy scale. Recent advancements have allowed us to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 36 publications
11
83
0
1
Order By: Relevance
“…However, TROPOMI SIF was considered for the purpose to fill the gaps left by OCO-2 in regions with spatial overlap. In a current study, Doughty et al [179] showed an increase in the plant photosynthesis process in terms of SIF during the dry season. The study was conducted over the tropical Amazonian forest using TROPOMI SIF datasets.…”
Section: Tropomi-related Sif Studiessupporting
confidence: 49%
“…However, TROPOMI SIF was considered for the purpose to fill the gaps left by OCO-2 in regions with spatial overlap. In a current study, Doughty et al [179] showed an increase in the plant photosynthesis process in terms of SIF during the dry season. The study was conducted over the tropical Amazonian forest using TROPOMI SIF datasets.…”
Section: Tropomi-related Sif Studiessupporting
confidence: 49%
“…This is likely at least in part due to its higher resolution, which among SIF products can currently only be matched by TROPOMI at a resolution of 7 × 3.5 km daily. TROPOMI SIF was recently used to track photosynthesis across California [ 71 ] as well as the dry season of the Brazilian Amazon [ 72 ], outperforming NIRv as a GPP-proxy. However, since 2018 was the first year that TROPOMI was operational, we did not investigate the signal from this satellite owing to a lack of preceding data with which to form a climatological period.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we calculated max(LC) to ensure the accuracy of the this study. With the launch of the OCO-3 (orbiting carbon observatory 3) satellite and the TROPOMI (TROPOspheric Monitoring Instrument) satellite with finer resolution [52]. An increasing amount of flux tower data are also public.…”
Section: Discussionmentioning
confidence: 99%